TRAP PRODUCTION AND REDUCTION LARVAE III HAEMONCHUS CONTORTUS BY NEMATOPHAGOUS MOULDS - Zainuddin Ahmad, Riza (Jurnal Veteriner; Vol 9 No 3 (2008), 2008)
A study was carried out to determine the ability of nematophagous moulds (Arthrobotrys oligosporaand Duddingtonia flagrans) to trap and reduce the number of H. contortus larvae III. Tests was conducted inpetri dishes containing agar medium, the moulds and Haemonchus contortus larvae. The ability of bothmould in trapping H. contortus larvae III was observed 3; 4; 10; 24 and 48 hours post-incubation, whereas theability of both mould in killing the larvae was observed 0,5; 3; 6; 9; 12; 15; 21; 24; 27 and 48 hours postincubation.The results showed that A. oligospora was more capable in trapping and reducing H. contortuslarvae III than Duddingtonia flagrans (p<0, 01). It was also evident that A. oligospora of Denmark originwas more capable in trapping and killing Haemonchus larve than that of local isolate. It is clear from thisstudy that A. oligospora is potential biological method for controling H. contortus infection in animals.
Keywords: Arthrobotrys oligospora, Duddingtonia flagrans, Haemonchus contortus larvae III, trap